Safety and tolerability of a single administration of AR-301, a human monoclonal antibody, in ICU patients with severe pneumonia caused by Staphylococcus aureus: first-in-human trial - François, Bruno; Mercier, Emmanuelle; Gonzalez, Céline; Asehnoune, Karim; Nseir, Saad; Fiancette, Maud; Desachy, Arnaud; Plantefève, Gaëtan; Meziani, Ferhat; de Lame, Paul-André; Laterre, Pierre-François (Intensive care medicine, 2018)
Purpose Hospital-acquired bacterial pneumonia (HABP) is a critical concern in hospitals with ventilator-associated bacterial pneumonia (VABP) remaining the most common infection in the ICU, often due to Staphylococcus aureus , an increasingly difficult to treat pathogen. Anti-infective monoclonal antibodies (mAb) may provide new, promising treatment options. This randomized, double-blinded, placebo-controlled study aimed at assessing the safety and pharmacokinetics of AR-301, an S. aureus alpha toxin-neutralizing mAb, and exploring its clinical and microbiologic outcomes when used adjunctively with standard-of-care antibiotics. Methods Eligibility in this trial required microbiologically confirmed severe S. aureus pneumonia, including HABP, VABP or CABP, treated in the ICU and an APACHE II score ≤ 30. Standard-of-care antibiotics selected by the investigators were administered to all patients in the study following clinical and microbiologic confirmation of S. aureus pneumonia. Adjunctive treatment of AR-301 was to start < 36 h after onset of severe pneumonia. AR-301 was administered to four sequentially ascending dose cohorts. The placebo cohort received antibiotics and a placebo buffer. Clinical outcomes were adjudicated by a blinded committee. S. aureus eradication was declared based on a negative follow-up culture and presumed to be negative when no culture was obtained in the presence of clinical improvement. Results Thirteen ICUs enrolled 48 patients, with pneumonia attributable to MRSA in six subjects. The study drug displayed a favorable safety profile: Of 343 AEs reported, 8 (2.3%) were deemed related, none serious. In a post hoc subgroup analysis of VABP patients receiving AR-301, ventilation duration was shorter for AR-301-treated patients compared with the placebo group. Overall, there was a trend toward a better and faster microbiologic eradication at day 28. The PK profile of AR-301 is consistent with that of a human IgG1 mAb, with a plasma half-life of about 25 days. Conclusions Adjunctive treatment of severe S. aureus HABP with anti-staphylococcal mAbs appears feasible and suggests some clinical benefits, but larger randomized studies are needed to better define its safety and efficacy.